The Dog That Barks Doesn't Bite: Coverage and Compliance of Sectoral Minimum Wages in Italy - Andrea Garnero (Institute of Labor Economics (IZA), 2017)
This paper provides a comprehensive portrait of the level and compliance to sectoral minimum wages in Italy between 2008 and 2015. The results show that minimum wages in Italy are relatively high both in absolute terms and relative to the median wage. However, non-compliance rates are not negligible: on average around 10% of workers are paid one fifth less than the reference minimum wage. Non-compliance is particularly high in the South and in micro and small firms and it affects especially women and temporary workers. Overall, wages in the bottom of the distribution appear to be largely unaffected by minimum wage increases. More effective enforcement practices are therefore needed to safeguard a level playing field for firms and ensure that minimum wage increases are effectively reflected into pay increases for workers at the bottom of the distribution.
Keywords: J08; J31; J52; J83; 330; collective bargaining; minimum wages; compliance